Application of Value Stream Mapping to Eliminate Waste in an Emergency Room (Global Journal of Medical Research, 2012)
Value Stream Mapping (VSM) is a lean/quality management tool which assists in establishing the current state of a process while aiding to uncover opportunities for improvement vis-#xE0;-vis the seven sources of waste. This research effort involves a review of existing literature pertaining to application of the VSM tool in hospital emergency rooms/departments. The paper will present the potential benefits emanating from application of VSM along with assessing its effectiveness in scenarios where it has been implemented already. Furthermore, challenges faced in implementation of the VSM tools are collated. Various solutions to address these challenges have been presented in the light of tribulations faced by today#x2019;s healthcare industry.
Keywords: departments; Stream; opportunities; potential